Root growth and yield responses to nitrogen levels in bell pepper (Capsicum annuum) cultivation: balancing nutrient efficiency and productivity - Chemweno, Sharon; Kwakye, Daniel Owusu; Rachmilevitch, Shimon; Ephrath, Jhonathan E.; Lazarovitch, Naftali (Frontiers in Plant Science, 2025)
IntroductionThe root system plays a key role in plant nutrient and water uptake, influencing growth, yield, and nitrogen use efficiency (NUE). However, excessive N fertilizer is often applied to boost productivity but can instead reduce efficiency and cause nitrate leaching, leading to underground water pollution. Optimizing N fertilization requires an understanding of root system response to nitrogen.MethodsWe examined the effect of different N rates on root growth using in situ minirhizotron (MR) and destructive root study methods (ingrowth core, soil core, and soil excavation). In a net-house experiment, bell peppers (Capsicum annuum) were examined under different N concentrations: 100 ppm (control), 50 ppm (moderate-N), and 25 ppm (low-N).ResultsReduced N concentrations reduced leaf gas exchange and shoot biomass, but promoted root growth. Across all four methods, root length density (RLD), total root length (TRL), and root surface area significantly increased under reduced N. RLD values in the upper 30 cm of the soil profile were significantly higher under the low and moderate-N treatments compared to the control treatment, while fine roots (<2 mm thickness) exhibited increased RLD with low-N treatment. MR system recorded a higher RLD of ~70% and 33% compared to ingrowth core and excavation, respectively, likely due to loss of fine roots during washing.DiscussionOur findings indicate that while reduced N application significantly enhanced root growth, resource allocation varied between low and moderate-N treatments. The moderate-N treatment achieved a balance, supporting both increased root development and yield. In contrast, the low-N treatment enhanced root growth and NUE but did not translate into higher yield. This suggests that N-induced root system plasticity is critical in optimizing nutrient uptake efficiency and ensuring balanced resource allocation for both root and shoot development, as demonstrated by the moderate-N treatment.